Benchmarking Process and Its Relationship with Organizational Performance - Hashim, Rushanim; Zien Yusoff, Rushaimi; Che Mat, Ruzinoor (School of Business and Management Institut Teknologi Bandung, 2008)
Benchmarking is recognized as an essential tool for continuous improvement of quality.Nowadays, many public sector organizations have been encouraged to implement benchmarking asone way of satisfying the government’s requirement that public organizations provide best valueservices. This paper begins with discussion of the literature that is integrated to point out the generalbasis of the topic. Then, this study will address the questions of whether the factors that affectingsuccessful benchmarking has relationship with benchmarking process as well as whetherbenchmarking process will lead to improvement of organizational performance. Therefore, the studyhad interviewed officers that involved in benchmarking project within 35 local authorities inPeninsular Malaysia. Finally, this paper also focuses on the methodology and data analysis of thestudy.Keywords: Benchmarking Process; Organizational Performance; Local Authorities